Acute Exercise Improves Inhibitory Control but Not Error Detection in Male Violent Perpetrators: An ERPs Study With the Emotional Stop Signal Task - Yu, Chia-Chuan; Chen, Chiao-Yun; Muggleton, Neil G.; Ko, Cheng-Hung; Liu, Suyen (Frontiers in Human Neuroscience, 2022)
Violence has been linked to the co-occurrence of cognitive dysfunction and altered activations in several brain regions. Empirical evidence demonstrated the benefits of acute exercise on motor inhibition and error detection as well as their neuronal processing. However, whether such effects also hold for the population with violent behaviors remains unknown. This study examined the effects of acute aerobic exercise on inhibitory control and error monitoring among violent offenders. Fifteen male violent offenders were counterbalanced into experimental protocols, which comprised a 30-min moderately aerobic exercise (60% heart rate reserve) and a 30-min reading control session. After each session, participants performed an emotional stop signal task while event-related potentials (ERPs) were recorded simultaneously. Results showed insignificant changes in ERPs components (i.e., N2, P3, ERN, and Pe amplitudes) and the behavioral performance in go condition, stop accuracy, and post-error adjustments by exercise. However, the current study demonstrated that the acute exercise facilitated stop signal reaction time compared to the control session regardless of emotional conditions. This is the first research to exhibit the improvements in inhibitory performance by acute exercise for violent offenders. Most importantly, this effect was independent of affective settings, expanding the existing knowledge of the influences of acute exercise on cognition. Our findings implicate the perspective of acute exercise for clinical and correctional practices.